The Effect Of Using Personal Vocabulary Notes Technique In Developing Students’ Vocabulary At Smpn 2 Besulutu - . Ikosusilowati (Cetta: Jurnal Ilmu Pendidikan, 2018)
This research aims at investigating the current level of students’ vocabulary ability before and after applying PVN technique and to find out whether there is a significant effect of using PVN technique on students’ vocabulary ability at the second year student of SMPN 2 Besulutu. This research applied pre-experimental design. This research was conducted in SMPN 2 Besulutu. The instrument of this research was reading test that focused on vocabulary. The population of this research was the second year student of SMPN 2 Besulutu who enrolled in academic year 2011/2012. The samples of this study were 22 students which were taken by using purposive sampling. The writer collected the data by giving vocabulary test were 40 items include multiple choice, cloze and classroom observation sheet. The result shows that the students’ vocabulary development on pre test was 5.37 while the students’ vocabulary development on post test was 7.35. The hypothesis testing was found that ttest = 15.02 which ttable=2.08 and degree of freedom (df ) = 21,and the significant α = 0.05. So, ttest> ttable or H0 was rejected and H1 was accepted. Therefore, it can be concluded that there was significant effect of using Personal Vocabulary Notes technique in developing students’ vocabulary at SMPN 2 Besulutu.